2018
DOI: 10.1038/s41598-018-33848-3
|View full text |Cite
|
Sign up to set email alerts
|

Donor-derived cell-free DNA is associated with acute rejection and decreased oxygenation in primary graft dysfunction after living donor-lobar lung transplantation

Abstract: Donor-derived cell-free DNA (dd-cf-DNA) has been shown to be an informative biomarker of rejection after lung transplantation (LT) from deceased donors. However, in living-donor lobar LT, because small grafts from blood relatives are implanted with short ischemic times, the detection of dd-cf-DNA might be challenging. Our study was aimed at examining the role of dd-cf-DNA measurement in the diagnosis of primary graft dysfunction and acute rejection early after living-donor lobar LT. Immediately after LT, marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…For the differential diagnosis of CLAD, a blood examination, plain chest X-ray, computed tomography of the chest, 6-min walk test, electrocardiography, and echocardiography were also performed at the same time as the pulmonary function testing and Q-scinti. Transbronchial biopsy was not performed to diagnose CLAD after LDLLT to avoid unexpected bleeding or pneumothorax from the small lobar grafts 16 . The study protocol (No.…”
Section: Methodsmentioning
confidence: 99%
“…For the differential diagnosis of CLAD, a blood examination, plain chest X-ray, computed tomography of the chest, 6-min walk test, electrocardiography, and echocardiography were also performed at the same time as the pulmonary function testing and Q-scinti. Transbronchial biopsy was not performed to diagnose CLAD after LDLLT to avoid unexpected bleeding or pneumothorax from the small lobar grafts 16 . The study protocol (No.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the technology used in prenatal screening, circulation of donor DNA in the serum of recipients can be found after allograft injury with cell apoptosis. [73][74][75] Recent studies have identified ddcfDNA as an important biomarker associated with AMR, and assays for quantifying the amount of donor DNA have been developed, serving as a noninvasive method to screen for allograft injury. These assays have been shown to have excellent sensitivity for acute rejection but relatively poor specificity.…”
Section: Future Areas Of Developmentmentioning
confidence: 99%
“…The dPCR technique proved to be more sensitive in detection of relapse after allo-HSCT compared to qPCR [35]. Similarly to allo-HSCT, dPCR has also been widely used in the context of SOT to detect dd-cfDNA in combination with DIPs [32,50], SNPs [3], copy number variations [51], or HLA-disparities [17,18,43,52].…”
Section: Comparison Of Microchimerism Detection Techniquesmentioning
confidence: 99%
“…The latter consists mainly of small sized (around 150 base-pairs) double-stranded DNA fragments resulting from apoptosis, necrosis, immune-mediated cell damage, or release of nuclear DNA into the circulation predominantly from hematopoietic cells [2]. In the circulation, these fragments have a short half-life of approximately 1.5 h due to rapid hepatic and renal clearance [3].…”
Section: Introductionmentioning
confidence: 99%